Visual Evoked Potential in Nepalese Patients with Oculocutaneous Albinism: A Case Series. - Shrestha, Gauri Shankar; Dahal, Hira Nath; Thapa, Madhu (Optometry & Visual Performance, 2019)
Purpose: Visual evoked potential (VEP) is an important non-invasive tool used to augment the functions of the visual system. The present study aims to present the VEP recorded among Nepalese subjects with oculocutaneous albinism (OCA) and its correlation with clinical findings. Methods: In a cross-sectional study, 10 consecutive subjects with OCA and 10 age-/sexmatched normal subjects were selected for a pattern reversal VEP test using the Retiscan Roland electrophysiological diagnostic system. Apart from VEP, OCA subjects' anterior and posterior segments were examined to record clinical findings. Contrast sensitivity with the Pelli-Robson chart, colour vision with the Farnsworth D-15 test, stereopsis with the Titmus vectographic plates, and cycloplegic refraction were also performed. Statistical analysis included paired t-test, independent sample t-test, and multiple linear regression analysis. Results: Clinical OCA features seen in study patients included horizontal pendular nystagmus in seven subjects, strabismus in four subjects, iris transillumination in seven subjects, disc hypoplasia in two subjects, and macular hypoplasia in four subjects. The mean VEP amplitudes were found to be significantly lower in subjects with albinism than in normal subjects in both right and left eyes for all frequencies. Strabismus (p<0.001 for N75-P100, low frequency; p<0.001 for N75-P100, high frequency; and p=0.021 for P100-N135, high frequency) and nystagmus (p=0.004 for P100-N135, high frequency and p=0.044 for P100-N135, low frequency) were significantly correlated with the amplitudes of pattern VEP. Mostly, P100-N135 high frequency was associated with clinical findings. Conclusion: The amplitude of pattern reversal VEP is significantly reduced in albinism, which is correlated with strabismus and nystagmus.